'Is it painful'? A qualitative study on experiences of patients before prostate needle biopsy. Issue 9 (8th September 2022) - Mao, Jinjiao; Dai, Yun; Wang, Lijuan; Pan, Shucheng; Wang, Wei; Yu, Hongwei
Abstract : Objective: To assess the experiences and emotional reactions of men prior to receiving a prostate needle biopsy (PNB). Design: This was a qualitative study involving (1) material research and filter, (2) interviewer training, (3) cognitive semistructured interviews with open-ended questions, (4) data analysis, including translation and back translation and (5) group discussions to determine common themes in the data. All interviews were digitally audio-recorded. The thematic analysis was conducted by repeatedly reading the data manuscript and engaging in group discussion. Setting and participants: A total of 30 participants with suspected prostate cancer (PC) who were scheduled to receive a PNB were interviewed. Eligible participants were Chinese native men aged 51–77 years, and the study was conducted in China between September and December 2020. All participants were informed about the purpose of the study and provided written informed consent. Results: Four main themes were identified based on the interview content: (1) fear (of pain, adverse effects and bad results), (2) impact of lower urinary tract symptoms (on emotional impact, work and sleeping), (3) inner struggles (relating to hesitation, regret and embarrassment) and (4) lifestyle change (including diet, exercise and receipt of traditional Chinese medicine). Conclusions: This patient cohort had a low level of knowledge about PC and PNB. Providing additional education about these topics would help to reduce patient fear and anxiety and improve experiences of the procedure.